Assessment of knowledge and attitude level regarding eye donation among community people of Mechinagar of Mechinagar-6, municipality, Jhapa, Province No. 1, Nepal. - Maharajan,Bijay (2018)
ABSTRACT: In Nepal opaque cornea is second major reason of blindness and cornea transplantation and grifting is best solution with high percentage of success rate. The objective of the study was to assess awareness level regarding the eye donation in Mechinagar Municipality ward no. 5 in Jhapa district. and attitude toward the eye donation. Descriptive research design was adopted for the study. Cross-sectional study was carried to assess the objective using questionnaire interview survey through probability systematic random sampling. All total 294 sample number was taken for the study. From the study it is concluded that in the study area around 40 percent people were found to have knowledge on eye donation and among them only 63 percent people had correct information and 37 out 1000 (3.7%) household were found willing to donate cornea. Religious believe as the challenge for the peoples participation is found to exist but is of non significant. Key Words: Eye donation. cornea transplantation, attitude and willingness